Zainab Afailal - The influence of AC and Ni/AC catalyst in the antioxidant additives production from argan shells lignin - Afailal, Zainab (Jornada de Jóvenes Investigadores del I3A, 2022)
The influence of AC and Ni/AC catalyst in the antioxidant additives production from argan shells lignin